Реализация позиции субъекта в автобиографическом нарративе - ПреображенскаяО. А. (Психология. Журнал Высшей школы экономики, 2011)
The article analyses the process of psychotherapeutic counselling, which is studied by both qualitative and quantitative methods. The author uses «narrative» for an objective indicator of counselling dynamic and «the subject of life span» to characterise the psychological component of changes that the client in counselling undergoes through. The author discusses the theoretical context of both categories, narrative and the subject’s position, and describes their elements. She gives the results of an empirical study that show a connection between the changes in the subject’s position and narrative in the process of counselling.